2019
DOI: 10.1002/pts.2430
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of antimony, cobalt, and acetaldehyde migration into the drinking water in Turkey

Abstract: Polyethylene terephthalate (PET) is a widely used material for the packaging of drinking water. The development of this research arises from the demand of a popular Turkish drinking water company, which has reported odour problems in their PET bottled products. Acetaldehyde, cobalt, and antimony contents were determined in bottled water of different volumes (0.5, 1.5, and 5 L), PET bottles, plastic blue closures, and preform material by gas chromatography mass spectrometry (GC‐MS) and inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The increase in levels of Antimony could be attributed to effects of pH, temperature and UV radiation (Fig. 2) from the sun, supported by experiments from (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019) which identified the significance of pH, temperature and days of exposure in the amount of Antimony leached into bottled water. The high level of the Antimony values can also be attributed to the type of plastics used by the different brands as identified by (Koyuncu and Alwazeer, 2019) who suspected reason for high Antimony levels in milk contained in PET bottles results from type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 74%
“…The increase in levels of Antimony could be attributed to effects of pH, temperature and UV radiation (Fig. 2) from the sun, supported by experiments from (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019) which identified the significance of pH, temperature and days of exposure in the amount of Antimony leached into bottled water. The high level of the Antimony values can also be attributed to the type of plastics used by the different brands as identified by (Koyuncu and Alwazeer, 2019) who suspected reason for high Antimony levels in milk contained in PET bottles results from type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 74%
“…The increase in the levels of antimony could be attributed to the effects of pH, temperature, and UV radiation (Fig. 2) from the Sun, supported by researchers who identified the significance of pH, temperature, and days of exposure in the amount of Antimony leached into bottled water (Al-Khatim et al, 2019;Chapa-Martínez et al, 2016;Dogan and Cebi, 2019;Zmit and Belhaneche-Bensemra, 2019). The high level of the antimony values can also be attributed to the type of plastics used by the different brands as identified by Koyuncu and Alwazeer (2019), who suspected that the reason for the high antimony levels in milk contained in PET bottles results from the type and production processes employed in making containers.…”
Section: Antimonymentioning
confidence: 77%
“…Antimony migration studies from PET into food products can provide useful information about the potential risk associated with its presence under different storage conditions. Several physicochemical factors, such as storage time, temperature, light irradiation, PET color, and matrix characteristics (e.g., pH and salt content), can influence Sb migration from PET containers to water samples [8][9][10][11]13,15,[17][18][19][20][21][22][23][24][25]. However, there is a wide variability in the effects of these factors on Sb migration [3], and the predominant role of the PET type or the water matrix is not clear [3,26,27].…”
Section: Introductionmentioning
confidence: 99%